Active alumina ball and preparation method and application thereof

By optimizing the pore structure and pore morphological characteristics of activated alumina and using amino-rich organic amines as modifiers, activated alumina balls with high carbon dioxide adsorption capacity and adsorption cycle stability were prepared, which solved the problem of insufficient carbon dioxide adsorption performance in the preparation of high-nickel ternary positive electrode materials, and achieved efficient carbon dioxide adsorption and cycle stability.

CN119869439AActive Publication Date: 2025-04-25HANGZHOU JIALONG AIR EQUIP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510346368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-25
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

During the preparation process, high-nickel ternary cathode materials are prone to react with water and carbon dioxide in the air, affecting the material performance. In the prior art, the carbon dioxide adsorption performance of activated alumina is relatively low, which limits the possibility of its independent application.

Method used

By optimizing the pore structure and pore morphological characteristics of activated alumina, using amino-rich organic amines as modifiers, the modifier is loaded to the inner pores and surfaces of the alumina powder by physical impregnation method to prepare activated alumina spheres with high carbon dioxide adsorption capacity and adsorption cycle stability.

Benefits of technology

While ensuring the compressive strength and specific surface area of ​​the sphere, the carbon dioxide adsorption capacity and adsorption cycle stability of the activated alumina sphere are greatly improved. It is suitable for compressed air decarbonization devices and reduces equipment manufacturing and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869439A_ABST
    Figure CN119869439A_ABST
Patent Text Reader

Abstract

The invention provides an activated alumina ball as well as a preparation method and application thereof. The preparation method comprises the following steps: 1) preparing alumina sol by taking pseudo-boehmite as an aluminum source; (2) carrying out hydroxyl reaction on a cross-linking agent and amylose molecules to prepare high polymer cross-linked starch with a spatial network structure; 3) drying, calcining, crushing and grinding the colloid to obtain alumina powder; 4) taking amino-rich organic amine as a modifier, and loading the modifier to the inner pores and the surface of the aluminum oxide by adopting a physical impregnation method; and 5) rolling to form balls by using a turntable balling method, and then hydrating and roasting to obtain the finished alumina spherulis.According to the activated alumina balls prepared by using the method, the pore channel structure and pore morphology characteristics are optimized, and the carbon dioxide adsorption capacity and the adsorption cycle stability of the activated alumina balls can be greatly improved while the compressive strength and the specific surface area of the balls are basically ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbent production, and in particular to an activated alumina ball and a preparation method and application thereof. Background Art

[0002] In recent years, high-nickel ternary materials, which have the advantages of high energy density, large discharge capacity and low comprehensive cost, have gradually become the main direction of lithium battery positive electrode material technology development. However, high-nickel ternary materials are very easy to react with water and carbon dioxide in the air during the preparation process to generate by-products, which affects the performance of such positive electrode materials. In response to the above problems, the invention patent of a compressed air decarbonization drying device and a method of use provided by China Patent Publication No. CN 118304741A discloses a purification device for reducing the carbon dioxide and moisture content in compressed air to meet the gas requirements for the preparation of high-nickel ternary positive electrode materials.

[0003] In the compressed air decarbonization drying device, molecular sieves are widely used because they are crystalline materials with regular and uniform pore structures, and their pore size is regulated accordingly with the molecular size, so that carbon dioxide molecules can be adsorbed through the microporous structure of the molecular sieve. However, due to the limited strength of molecular sieves, and the adsorption performance and separation effect under high humidity conditions are inferior to those of activated alumina, it is often necessary to place part of the activated alumina at the bottom of the molecular sieve bed to absorb moisture and resist the impact of airflow. However, in the actual use of compressed air decarbonization drying devices, this method requires the use of activated alumina and molecular sieve double-layer bed process, which not only leads to complex structure of the adsorber, high cost, and mixed bed risk; on the other hand, although activated alumina has a large specific surface area and good chemical stability, its low carbon dioxide adsorption performance limits its possibility of independent application in compressed air decarbonization drying devices.

[0004] Based on the above reasons, improving the adsorption capacity of activated alumina for carbon dioxide by physical or chemical methods has gradually become an important way to solve the above problems. At present, in the field, the research on using activated alumina as raw material, ethanol solution of pentaethylenehexamine as modifier and using impregnation method to prepare modified activated alumina to improve the carbon dioxide adsorption capacity of activated alumina has made certain progress, but limited by the uneven pore size distribution and complex pore morphology of the carrier activated alumina, the activated alumina balls prepared by the above method still generally have problems such as limited improvement in adsorption performance and low adsorption sequence stability. Summary of the invention

[0005] The purpose of the present invention is to provide an activated alumina ball and a preparation method and application thereof. By optimizing the pore structure and pore morphology characteristics of the activated alumina, its ability and effect of loading amino-rich organic amines are improved, and while basically ensuring the compressive strength and specific surface area of ​​the sphere, its carbon dioxide adsorption capacity and adsorption cycle stability can be greatly improved.

[0006] like Figure 1 To achieve the above purpose, the present technical solution provides a method for preparing activated alumina balls, comprising the following steps: S1: adding pseudo-boehmite into deionized water at a temperature of 85-95° C. and stirring the mixture thoroughly to obtain a liquid-solid mixture slurry, adding nitric acid to the liquid-solid mixture slurry, stirring the mixture under a constant temperature, and aging and refluxing the mixture to obtain an aluminum sol; S2: adding starch and sodium hydroxide solution into deionized water and stirring to obtain an alkaline starch suspension, adding a crosslinking agent to the alkaline starch suspension and reacting at 20-55° C. for a period of time, followed by filtering, washing and drying in sequence to obtain a high polymer cross-linked starch having a spatial network structure; S3: mixing the polymer cross-linked starch with the aluminum sol, and then drying, calcining, crushing, and grinding the mixture to obtain aluminum oxide powder; S4: using physical impregnation to load the modifier into the inner pores and surface of the alumina powder to obtain modified activated alumina powder, wherein the modifier is an organic amine rich in amino groups; S5: spraying an aqueous solution containing an additive or a binder into a spheroidizing plate containing modified activated alumina powder and forming spheroids by a rotating plate spheroidizing method, rehydrating and calcining the spheroids to obtain activated alumina spheres.

[0007] Step S1 of this scheme uses pseudo-boehmite as a raw material, and uses the peptization characteristics of pseudo-boehmite under acidic conditions to form a stable aluminum sol, which provides a basic raw material for the subsequent preparation of activated alumina, and its pore structure and morphology are conducive to subsequent amino modification. It should be noted that pseudo-boehmite is a kind of incompletely crystallized boehmite, has a chemical composition similar to that of boehmite, contains 1.25~2.0 crystal waters, is a type of incompletely crystallized hydrated aluminum oxide, also known as monohydrated aluminum oxide, pseudo-monohydrate soft aluminum oxide, and the typical structure of pseudo-boehmite is an extremely thin pleated sheet, which is an aluminum oxide hydrate with a special spatial network structure, and has physical properties such as high specific surface area and large pore volume, and chemical properties of peptization and thixotropy under acidic conditions.

[0008] In some embodiments, pseudo-boehmite is prepared by any one of the following methods: gibbsite quick stripping method, aluminum salt neutralization method, alcohol aluminum method, alkali method, and nitric acid method. The specific preparation process is selected according to the source of the raw materials and the product performance.

[0009] In some embodiments, the grain size of pseudo-boehmite is 3.5-6.0 nm. The appropriate grain size helps to form a uniform aluminum sol, thereby better controlling the pore structure and morphology of the activated alumina balls in subsequent processes, thereby ensuring the consistency and stability of product performance.

[0010] In some embodiments, pseudo-boehmite is added to deionized water at a temperature of 85-95°C and fully stirred, wherein the stirring conditions are set to a stirring speed of 600-900 r / min, an aging time of 5-8 hours, and a reflux time of 2-3 hours, which can enable the pseudo-boehmite to be fully dispersed and reacted, promote the formation and stabilization of aluminum sol, and ensure the quality and performance of aluminum sol.

[0011] In some embodiments, the solid content in the liquid-solid mixture slurry is 60-80 g / L, which ensures the appropriate concentration of pseudo-boehmite in the reaction system, avoiding uneven reaction or excessive viscosity of the system due to excessively high concentration, and preventing production efficiency and product quality from being affected by excessively low concentration.

[0012] In some embodiments, nitric acid with a concentration of 3-5% is added to the liquid-solid mixture slurry at an acid-aluminum molar ratio of 0.06-0.1:1. The appropriate amount and concentration of nitric acid can ensure sufficient peptization of pseudo-boehmite while avoiding the adverse effects of excessive or insufficient nitric acid on the structure and properties of the aluminum sol, thereby ensuring the stability of the aluminum sol and the quality of subsequent products.

[0013] In step S2 of this scheme, starch and sodium hydroxide solution are mixed to obtain an alkaline starch suspension, and a cross-linking agent is added for reaction, followed by filtration, water washing and drying to obtain a high polymer cross-linked starch having a spatial network structure. The starch selected in this scheme is straight-chain starch to avoid excessive viscosity of the mixed system. The spatial network structure formed by the cross-linking reaction helps to regulate the pore structure of activated alumina during the subsequent mixing and treatment process with aluminum sol.

[0014] It should be noted that cross-linked starch is a new synthetic substance, which belongs to a type of modified starch; it is also an important starch derivative, which is formed by a cross-linking agent containing binary or polyfunctional groups reacting with starch molecules to form hydroxyl groups (generating diether bonds, diester groups, etc.), thereby cross-linking two or more starch molecules to form a high polymer cross-linked starch with a spatial network structure. Natural starch is composed of amylose and amylopectin, and most starches contain 10% to 12% amylose and 80% to 90% amylopectin. Corn starch contains 27% amylose; potato starch contains 20% amylose (the rest of both are amylopectin); glutinous rice starch is almost entirely amylopectin. In the present invention, amylose is used as the starch raw material to prepare the high polymer cross-linked starch, which has a relatively simple molecular structure, a small molecular weight, high solubility and stability, and a relatively low viscosity, which can avoid the excessive viscosity of the mixed system of activated alumina during the preparation process and agglomeration, and relatively improve the smoothness of the mixed system.

[0015] In some embodiments, the starch in step S2 is amylose, selected from one or more of mung bean starch, soybean starch, white bean starch or reversed starch.

[0016] In some embodiments, the starch content in the alkaline starch suspension is 90-130 g / L, and the pH value is 7.6-9. This starch content range can ensure that there is enough starch participation in the cross-linking reaction to form a suitable spatial network structure. If the content is too low, the cross-linking effect is not good, and the pore structure of the activated alumina cannot be effectively regulated; if the content is too high, the viscosity of the system may be too high, affecting the reaction and product performance. The suitable pH environment provides good conditions for the cross-linking reaction, which can promote the reaction of the cross-linking agent with the hydroxyl group of the starch molecules, so that the cross-linking reaction proceeds smoothly, and helps to form a stable and ideal spatial network structure of polymer cross-linked starch, which in turn has a positive effect on the pore structure of the activated alumina.

[0017] In some embodiments, the crosslinking agent is epichlorohydrin, trisodium metaphosphate or hexametaphosphate. These crosslinking agents contain binary or polyfunctional groups, which can react with starch molecules to form diether bonds, diester groups and other groups, cross-linking two or more starch molecules to form a stable spatial network structure. This structure can act as a template during mixing with aluminum sol, subsequent drying, calcination, etc., and help regulate the pore structure of activated alumina to make it more regular and uniform.

[0018] In some embodiments, the mass fraction of the crosslinking agent is 0.2-3% of the mass fraction of the starch. This addition ratio can ensure that the crosslinking agent fully reacts with the starch to form an effective spatial network structure, while not causing excessive crosslinking due to excessive crosslinking agent, thereby affecting the performance of the starch and the subsequent synergistic effect with the aluminum sol; nor will it cause insufficient crosslinking reaction due to insufficient crosslinking agent, thereby failing to achieve the expected pore regulation effect.

[0019] In some embodiments, a crosslinking agent is added to the alkaline starch suspension and reacted for 3 to 4 hours. This reaction time can ensure that the crosslinking agent fully reacts with the starch molecules so that the spatial network structure can be fully formed and stabilized. If the reaction time is too short, the crosslinking reaction is incomplete and the pores of the activated alumina cannot be effectively regulated; if the reaction time is too long, it may lead to excessive crosslinking, causing changes in the starch structure and affecting product performance.

[0020] In step S3 of this scheme, the polymer cross-linked starch is mixed with the aluminum sol, and then dried, calcined, crushed, and ground to obtain alumina powder. It should be noted that the sol-gel method uses a compound containing a highly chemically active component as a precursor, uniformly mixes these raw materials in a liquid phase, and undergoes hydrolysis and condensation chemical reactions to form a stable transparent sol system in the solution. After aging, the sol particles slowly polymerize to form a gel with a three-dimensional network structure. The gel network is filled with a solvent that has lost fluidity to form a gel. The gel is dried, sintered, and solidified to prepare a molecular or even nano-substructured material. In the present invention, the active alumina pore structure and morphological characteristics prepared by the sol-gel method using pseudo-boehmite as the aluminum source are more suitable for amino modification using a physical impregnation method.

[0021] In some embodiments, the mass ratio of polymer cross-linked starch to aluminum sol is (1.1-1.4): 50. At this mass ratio, the cross-linked starch is evenly dispersed in the aluminum sol system, and the spatial network structure formed by the cross-linked starch acts as a template in the subsequent drying and calcination process. During high-temperature treatment, the cross-linked starch gradually decomposes, leaving evenly distributed pores. These pores cooperate with the alumina skeleton formed by the aluminum sol to help form a regular, uniform and suitable pore structure, providing a good diffusion channel for gas molecules such as carbon dioxide, improving the adsorption efficiency, and optimizing the pore structure of the alumina powder. And the appropriate ratio can ensure that in the process of forming activated alumina balls, neither too much impurities will remain after calcination due to excessive cross-linked starch, affecting the specific surface area, nor will the pore structure be effectively regulated due to too little cross-linked starch, thereby ensuring that the activated alumina balls have a higher specific surface area. A larger specific surface area means more active sites, which can enhance the adsorption capacity of carbon dioxide.

[0022] In some embodiments, in step S3, the drying temperature is 110-180°C, and the drying time is 2-8 hours; the calcination temperature is 550-650°C, and the calcination time is 4.5-6 hours. Furthermore, the calcination process firstly increases the temperature to 330-350°C at a heating rate of 2.5-3.3°C / min, and keeps the temperature constant for 0.5-1 hour, and then increases the temperature to 550-650°C at a heating rate of 1.7-2.2°C / min under oxygen flow and keeps the temperature constant for 1-2 hours.

[0023] In some embodiments, the alumina powder prepared in step S3 has a particle size of 320 mesh to 550 mesh.

[0024] In step S4 of this scheme, an organic amine rich in amino groups is used as a modifier, and is loaded into the inner pores and surface of the alumina powder by a physical impregnation method. The amino groups in the organic amine can react with carbon dioxide to form carbamates, thereby enhancing the adsorption capacity of activated alumina for carbon dioxide. It should be noted that the organic amine molecules can be amino-modified for activated alumina, and the affinity of activated alumina for CO2 can be enhanced by the large amount of amino groups they contain, and react with CO2 to form carbamates. Although the organic amine molecules are successfully loaded on the activated alumina without destroying the original structure of the activated alumina, their specific surface area and pore volume are slightly reduced.

[0025] In some embodiments, the organic amine is one or more selected from tetraethylene pentamine, pentaethylene hexamine, hexaethylene heptamine, polyethylene polyamine, and hydroxyethyl ethylene diamine, which can maintain better recycling ability and is more suitable for forming impregnated amino solids.

[0026] In step S5 of this scheme, an aqueous solution containing an additive or a binder is sprayed into the modified activated alumina powder, and the powder is formed into balls by a rotating disk ball forming method, and then hydrated and roasted. The additive or the binder helps the powder to form balls, hydration can further optimize the internal structure of the activated alumina balls, and roasting can remove impurities, adjust the pore structure and morphology, improve product performance, and make the activated alumina balls have specific compressive strength, specific surface area and carbon dioxide adsorption performance.

[0027] It should be noted that the calcination process is also one of the important factors affecting the pore structure and morphology of activated alumina. Calcination includes dehydration, dehydroxylation, particle sintering, decomposition or removal of volatile substances and burning of organic matter, all of which affect the pore structure and morphology of the final activated alumina carrier. At different calcination temperatures, the pore structure of activated alumina will continue to change.

[0028] The test results show that as the calcination temperature increases, smaller pores collapse to form larger pores, the average pore size gradually increases, and the corresponding specific surface area gradually decreases. When the calcination temperature is 380~450℃, activated alumina with high specific surface area and large pore volume can be obtained. In addition, the appropriate adjustment of the heating rate can completely remove the moisture in the small pores, thereby eliminating agglomeration and fracture. Therefore, in order to ensure the properties of the activated alumina carrier, the appropriate calcination temperature and calcination time must be controlled in its calcination process. In some embodiments, the calcination temperature is 380~450℃, and the calcination time is 30~40min.

[0029] In a second aspect, the present invention provides an activated alumina ball, which is prepared according to the preparation method of the activated alumina ball mentioned in the first aspect.

[0030] In some embodiments, the pore morphology of most of the pores of the activated alumina ball is a straight cylinder, and the specific surface area is ≥280m 2 / g, strength greater than 150N / particle; under the operating temperature of 25℃ and the operating pressure of 250mmHg, the saturated adsorption capacity of CO2 is ≥6wt%.

[0031] In a third aspect, the present invention provides a compressed air decarbonization device, which uses the activated alumina balls as adsorbent.

[0032] In some embodiments, the compressed air decarbonization device is used in the high-nickel ternary positive electrode material preparation scenario to reduce the carbon dioxide and moisture content in the compressed air.

[0033] Compared with the prior art, this technical solution has the following characteristics and beneficial effects: (1) The present invention uses pseudo-boehmite as an aluminum source to prepare porous activated alumina, and then uses an organic amine rich in amino groups as a modifier. The activated alumina balls prepared by the impregnation method have a uniform pore size distribution, which also provides sufficient confined space for the amine modifier, prompting the amine modifier to form a highly spatially dispersed state, thereby exposing more hydrophilic groups. Compared with ordinary activated alumina balls, they have a higher carbon dioxide adsorption effect, can be recycled, and have high stability.

[0034] (2) The present invention effectively improves the pore structure and morphology characteristics of activated alumina balls through reasonable selection and ratio of raw materials, cross-linking agents, and modifiers, and optimizes process parameters in terms of gelatin making, drying, cross-linking, calcination, modification, and activation, thereby ensuring basic performance indicators such as spherical compressive strength, specific surface area, and static adsorption capacity. It should be noted that the pore structure and morphology characteristics of the adsorbent have a very important influence on its adsorption and desorption performance. According to different shapes, the adsorbent pores can be mainly divided into spherical pores, conical pores, cylindrical pores, and fissure pores. The use of straight-chain cross-linked starch as a pore-forming agent can make activated alumina produce cylindrical pores that are more conducive to the implementation of the impregnation process. Through the analysis of the adsorbent performance experimental test data, the improvement of the carbon dioxide adsorption performance and cycle stability of activated alumina is mainly due to this.

[0035] (3) The present invention provides a method for producing activated alumina balls which has a simple and efficient preparation process, low cost, and is easy to scale up. The products prepared by this method can effectively achieve synchronous and efficient adsorption of water and carbon dioxide, greatly reducing the manufacturing cost and maintenance cost of compressed air decarbonization equipment and similar equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the process roadmap for the preparation method of activated alumina balls provided in this scheme. DETAILED DESCRIPTION

[0037] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0038] Example 1 Weigh 7g of pseudo-boehmite and add it to 100ml of deionized water, stir it thoroughly at 90℃ to prepare a liquid-solid mixture slurry; add 3.5% dilute nitric acid to the slurry at an acid-aluminum molar ratio of 0.06:1, stir it at a constant temperature of 800r / min, age it for 5.5h, reflux it for 3h, and obtain aluminum sol for use; Weigh 5g of mung bean starch and add sodium hydroxide aqueous solution A (0.05mol / L) to prepare a starch milk with a mass fraction of 12%, and adjust the pH value to 8.5 with sodium hydroxide aqueous solution B (mass fraction of 2%). Slowly add 1.5mL of sodium hexametaphosphate solution (mass fraction of 4%) to the starch milk. After the cross-linking reaction is completed, take out the product, filter it, wash it with water, and let it stand in an oven at 40℃ for 3.5h to obtain cross-linked starch.

[0039] The cross-linked starch and the reserved aluminum sol are mixed in a mass ratio of 1.2:50, and the obtained colloid is dried at a constant temperature of 160°C for 4 hours, then gradually heated to 350°C at a heating rate of 3°C / min, kept at a constant temperature for 0.5 hours, and then heated to 650°C at a heating rate of 2°C / min under oxygen flow and kept at a constant temperature for 2 hours, and then crushed and ground to a powder particle size of 400 mesh.

[0040] Dissolve 2g of tetraethylenepentamine in 50mL of anhydrous ethanol, and stir at a constant temperature of 40°C until it is completely dissolved. Weigh 5g of activated alumina, place it in the above stirred solution, and stir at a constant temperature of 40°C for 4h. Filter and wash the impregnated activated alumina, and dry it in a vacuum drying oven at -0.095MPa and 85°C for 12h to obtain tetraethylenepentamine modified activated alumina.

[0041] Take 15g of ammonium bicarbonate and 8g of sodium carbonate and add them to 100ml of deionized water, and stir them thoroughly to form a binder slurry. Place the modified activated alumina powder in a rotating ball-forming plate and spray the binder slurry to make the powder adhere to each other and gradually form spherical particles during rolling. After the formed balls are stored in a greenhouse for 24 hours, they are hydrothermally treated with 120℃ steam for 2 hours. Then, the hydrothermally treated balls are roasted at 450℃ for 30 minutes to obtain finished activated alumina balls.

[0042] Example 2 Weigh 7 g of pseudo-boehmite and add it to 100 ml of deionized water, stir it thoroughly at 85° C. to prepare a liquid-solid mixture slurry; add 5% dilute nitric acid to the slurry at an acid-aluminum molar ratio of 0.08:1, stir it at a constant temperature of 800 r / min, age it for 6.5 h, reflux it for 3 h, and obtain aluminum sol for use; Weigh 5g of soybean starch and add sodium hydroxide aqueous solution A (0.05mol / L) to prepare a starch milk with a mass fraction of 12%, and adjust the pH value to 9 with sodium hydroxide aqueous solution B (mass fraction of 3%). Slowly add 2.4mL of epichlorohydrin solution (mass fraction of 2%) to the starch milk. After the cross-linking reaction is completed, take out the product, filter it, wash it with water, and let it stand in an oven at 40℃ for 3.5h to obtain cross-linked starch.

[0043] The cross-linked starch and the reserved aluminum sol are mixed in a mass ratio of 1.3:50, and the obtained colloid is dried at a constant temperature of 160°C for 4 hours, then gradually heated to 330°C at a heating rate of 2.5°C / min, kept at a constant temperature for 1 hour, and then heated to 550°C at a heating rate of 1.8°C / min under oxygen conditions and kept at a constant temperature for 1.5 hours, and then crushed and ground to a powder particle size of 500 mesh.

[0044] Dissolve 2.5g of pentaethylenehexamine in 50mL of anhydrous ethanol, and stir at a constant temperature of 40°C until it is completely dissolved. Weigh 5g of activated alumina, place it in the above stirred solution, and stir at a constant temperature of 40°C for 4h. Filter and wash the impregnated activated alumina, and dry it in a vacuum drying oven at -0.095MPa and 85°C for 12h to obtain pentaethylenehexamine modified activated alumina.

[0045] Take 15g of ammonium bicarbonate and 8g of sodium carbonate and add them to 100ml of deionized water, and stir them thoroughly to form a binder slurry. Place the modified activated alumina powder in a rotating ball-forming plate and spray the binder slurry to make the powder adhere to each other and gradually form spherical particles during rolling. After the formed balls are stored in a greenhouse for 24 hours, they are hydrothermally treated with 120℃ steam for 3h. Then, the hydrothermally treated balls are roasted at 400℃ for 30min to obtain finished activated alumina balls.

[0046] Example 3 Other raw materials, components and parameters were the same as those in Example 1, except that the type, specification and quantity of the cross-linking agent were changed from 1.5 mL of sodium hexametaphosphate solution (4%) to 2.4 mL of epichlorohydrin solution (mass fraction: 2%); and the type of starch was changed from mung bean starch to white bean starch.

[0047] Example 4 Other raw materials, components and parameters are the same as those in Example 1, except that the type of organic amine is changed from tetraethylenepentamine to pentaethylenehexamine.

[0048] Example 5 Other raw materials, components and parameters were the same as those in Example 1, except that 1.5 mL of sodium hexametaphosphate solution (4%) was added dropwise after the pH value of the alkaline starch suspension was adjusted to 10.5.

[0049] Example 6 Other raw materials, components and parameters are the same as those in Example 2, except that during the preparation of the aluminum sol, dilute nitric acid is added at an acid-aluminum molar ratio of 0.08:1.

[0050] Example 7 Other raw materials, components and parameters are the same as those in Example 2, except that pentaethylenehexamine is replaced by hexaethyleneheptamine.

[0051] Comparative Example 1 Other raw materials, components and parameters are the same as those in Example 1, except that the mixing mass ratio of the cross-linked starch to the standby aluminum sol is changed from 1.2:50 to 0.8:50.

[0052] Comparative Example 2 Other raw materials, components and parameters were the same as those in Example 2, except that the amount of epichlorohydrin solution (mass fraction: 2%) added was changed from 2.4 mL to 1 mL.

[0053] Comparative Example 3 The other parameters and steps are the same as those in Example 1, but without adding cross-linked starch, the aluminum sol is directly dried, calcined, crushed, ground and modified in sequence.

[0054] Performance testing: The activated alumina balls prepared in the above Examples 1 to 7 and Comparative Examples 1 to 3 were filled in adsorption tubes respectively, and high-purity nitrogen at a temperature of 250° C. was introduced for heating and activation for 1 h. After closed cooling, the compressive strength, specific surface area, and static water adsorption capacity were tested in accordance with the "HG / T3927-2020 Industrial Activated Alumina" standard; the CO2 static adsorption capacity was tested with reference to the "HG / T2690-2012 13X Molecular Sieve", and then the sample was heated and regenerated in a vacuum, and the above steps were repeated 10 times. The adsorption-desorption cycle stability of the activated alumina ball sample was evaluated according to the mass change amplitude of the activated alumina ball sample in each adsorption-desorption cycle process, and the test results of each embodiment and comparative example were obtained as shown in Table 1 below: Table 1 Test results of various embodiments and comparative examples

[0055] It can be seen from the test results that the activated alumina balls obtained according to the preparation method of the present application can greatly improve the static adsorption capacity of carbon dioxide and the adsorption cycle stability while basically ensuring the compressive strength and static water adsorption capacity of the balls.

[0056] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A method for preparing activated alumina balls, characterized in that: The following steps are involved: S1: adding pseudo-boehmite into deionized water at a temperature of 85-95° C. and stirring the mixture thoroughly to obtain a liquid-solid mixture slurry, adding nitric acid to the liquid-solid mixture slurry, stirring the mixture under a constant temperature, and aging and refluxing the mixture to obtain an aluminum sol; S2: adding starch and sodium hydroxide solution into deionized water and stirring to obtain an alkaline starch suspension, adding a crosslinking agent to the alkaline starch suspension and reacting at 20-55° C. for a period of time, followed by filtering, washing and drying in sequence to obtain a high polymer cross-linked starch having a spatial network structure; S3: mixing the polymer cross-linked starch with the aluminum sol, and then drying, calcining, crushing, and grinding the mixture to obtain aluminum oxide powder; S4: using physical impregnation to load the modifier into the inner pores and surface of the alumina powder to obtain modified activated alumina powder, wherein the modifier is an organic amine rich in amino groups; S5: spraying an aqueous solution containing an additive or a binder into a spheroidizing plate containing modified activated alumina powder and forming spheroids by a rotating plate spheroidizing method, rehydrating and calcining the spheroids to obtain activated alumina spheres.

2. The method for preparing activated alumina balls according to claim 1, characterized in that: Pseudo-boehmite is added into deionized water at a temperature of 85-95°C and stirred thoroughly, wherein the stirring conditions are set at a stirring speed of 600-900 r / min, an aging time of 5-8 h, and a reflux time of 2-3 h.

3. The method for preparing activated alumina balls according to claim 1, characterized in that: Nitric acid with a concentration of 3-5% is added to the liquid-solid mixture slurry at an acid-aluminum molar ratio of 0.06-0.1:

1.

4. The method for preparing activated alumina balls according to claim 1, characterized in that: The starch is straight-chain starch, the cross-linking agent is epichlorohydrin, trisodium metaphosphate or hexametaphosphate, and the mass fraction of the cross-linking agent is 0.2-3% of the mass fraction of the starch.

5. The method for preparing activated alumina balls according to claim 1, characterized in that: The starch content in the alkaline starch suspension is 90~130g / L, and the pH value is 7.6~9.

6. The method for preparing activated alumina balls according to claim 1, characterized in that: The mass ratio of polymer cross-linked starch to aluminum sol is (1.1~1.4):

50.

7. The method for preparing activated alumina balls according to claim 1, characterized in that: The organic amine is one or more selected from tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, polyethylenepolyamine, and hydroxyethylethylenediamine.

8. The method for preparing activated alumina balls according to claim 1, characterized in that: The calcination temperature is 380~450℃ and the calcination time is 30~40min.

9. An activated alumina ball, characterized in that: The activated alumina balls are prepared according to the preparation method of any one of claims 1 to 8.

10. A compressed air decarbonization device, characterized in that: The activated alumina balls according to claim 9 are used as adsorbent.

Citation Information

Patent Citations

  • Compressed air decarburization drying device and using method

    CN118304741A

  • Preparation method of catalytic heat carrier and application of catalytic heat carrier in self-heating pyrolysis liquefaction

    CN113617360A

  • Alumina carrier and preparation method thereof

    CN113663699A

  • Alumina carrier as well as preparation method and application thereof

    CN116037217A

  • Alumina ceramic powder and preparation process thereof

    CN119176713A